Ain Shams University- Paving the way towards a paperless University - Elagroudy, Sherien; Elbardisy, Wesam M; Hassan, Ghada F; Saoud, Abdelfattah; El-Meteini, Mahmoud A.S. (Universitas Diponegoro, 2023)
The conventional use of paper-based operations in daily working practices introduces numerous risks and financial burdens. Nowadays, Universities are aligning with the growing movement of